Isolation and expression of gene encoding leucoanthocyanidin reductase from Diospyros kaki during fruit development - Y. Wang; Q. L. Zhang; Z. R. Luo (Biologia Plantarum, 2010)
Leucoanthocyanidin reductase (LAR) converts leucoanthocyanidin to (+)-catechin, a precursor of proanthocyanidins abundant in Japanese persimmon (Diospyros kaki Thunb.) fruits. A putative LAR gene (DkLAR) was isolated by rapid amplification of cDNA ends from young fruits. The full-length cDNA of DkLAR gene was 1 356 bp long and encoded an open reading frame of 349 residues. The deduced DkLAR protein was closely related to the homolog in other plant species. The expression of the DkLAR gene in Chinese pollination-constant non-astringent (PCNA) genotype was coincident with the tannin cell development, but was not in Japanese PCNA and Chinese pollination-variant astringent (PCA) genotypes.